2015
DOI: 10.1002/jmv.24239
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in cytomegalovirus genotype in immunocompetent patients with corneal endotheliitis or iridocyclitis

Abstract: Cytomegalovirus (CMV) that caused corneal endotheliitis and iridocyclitis in immunocompetent patients was genotyped. The gB type1 was detected in seven endotheliitis samples (77.8%) and five iridocyclitis samples (100%), and the gB type 3 was detected in two endotheliitis samples (22.2%). The UL144 type 1 was found in five endotheliitis samples (45.5%) and five iridocyclitis samples (83.3%). The UL144 type 2 was found in two endotheliitis samples (18.2%) and one iridocyclitis sample (16.7%). The gB type 1 was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 22 publications
3
8
0
1
Order By: Relevance
“…CMV viral load is also known to be associated with corneal endothelial cell damage in CMV anterior uveitis and corneal endotheliitis 17 23. Similar CMV genotypes have been detected in eyes with corneal endotheliitis and anterior uveitis;24 therefore, sufficient and sustainable reductions of CMV in the corneal endothelium and aqueous humour might be beneficial for preventing irreversible corneal endothelial dysfunction in the long term in patients with primary CMV endotheliitis and post-keratoplasty patients with CMV endotheliitis.…”
Section: Discussionmentioning
confidence: 82%
“…CMV viral load is also known to be associated with corneal endothelial cell damage in CMV anterior uveitis and corneal endotheliitis 17 23. Similar CMV genotypes have been detected in eyes with corneal endotheliitis and anterior uveitis;24 therefore, sufficient and sustainable reductions of CMV in the corneal endothelium and aqueous humour might be beneficial for preventing irreversible corneal endothelial dysfunction in the long term in patients with primary CMV endotheliitis and post-keratoplasty patients with CMV endotheliitis.…”
Section: Discussionmentioning
confidence: 82%
“…We found that the distribution of UL144 genotypes in our cohort ( Table 7 ) was significantly different from the distribution in Illinois, USA [ 21 ], Europe [ 23 , 26 , 27 , 38 ], Taiwan [ 7 ], and even Shenyang, China [ 5 ], but similar to the distribution in Tennessee, USA [ 19 ] and The Netherlands [ 39 ]. We noted, however, that the distribution of UL144 genotypes was similar in Japan and Taiwan [ 7 , 22 ]. Similarly, the distribution of UL146 genotypes in our cohort was significantly different from the distribution in the UK [ 29 ], Poland [ 6 ], and Japan [ 40 ], in which G2 or G1 is predominant along with G7.…”
Section: Resultsmentioning
confidence: 99%
“…The molecular epidemiology of American [ 19 ], Japanese [ 22 , 40 ], Italian [ 6 , 26 ], and Polish [ 23 ] isolates has been investigated based on UL144 and UL146. In addition, Waters et al .…”
Section: Discussionmentioning
confidence: 99%
“…Currently, it remains unclear whether the endotheliitis type and the anterior uveitis type of CMV are caused by different CMV strains. However, Oka et al reported no significant difference in the amount of viral load or viral protein profiles for these two types of diseases [ 22 ].…”
Section: Discussionmentioning
confidence: 99%